Estudo da estrutura de nanoilhas de grafeno por microscopia de varredura por tunelamento - Sofia de Oliveira Parreiras (2017)
The epitaxial growth of graphene over metallic surfaces is one of the promising methods for the developing of technological applications. Due to the small mismatch between the two lattices and the strong interaction, the Ni(111) substrate is particularly interesting for the controlled growth of isolated graphene nanoislands with well-defined morphologies (triangular or hexagonal). The size reduction to the nanometer scale modifies the nucleation and growth mechanisms stabilizing different types of edges depending on the atomic stacking. This offers the possibility to synthesize structures that are exclusive to the nanoscale, but also calls for fundamental growth studies in order to control them. High-resolution Scanning Tunneling Microscopy images were used to study graphene nanoislands grown on Ni(111) by chemical vapor deposition and postannealing at different temperatures. The atomic stacking configurations, domain boundaries, and edge structure of the nanoislands were determined. We find a nonconventional multistep mechanism that separates the thermal regimes for growth, edge reconstruction, and final stacking configuration, leading to nanoisland morphologies that are incompatible with their stacking symmetry. Whole islands shift their stacking configuration during cooling down, and others present continuous transitions at the edges. A statistical analysis of the domain structures obtained at different annealing temperatures reveals how polycrystalline, ill-defined structures heal into shape-selected islands of a single predominant stacking. Additionally, the effect of the surface alloying on the structural properties of graphene nanoislands was investigated. Fe-Ni and Co-Ni alloys modify the energy equilibrium of the edges, leading to changes on the islands morphologies. It was observed that the islands prepared on alloys, in general, exhibit a polycrystalline structure, but the distribution of domains is altered.